31° South: Dietary niche of an arid‐zone endemic passerine. Issue 2 (31st May 2019) - Ribeiro, Ângela M.; Smit, Ben; Gilbert, M. Thomas P.
Abstract: Balancing energy budgets are thought to be challenging for birds living in arid ecosystems because food supplies are low and unpredictable, and climatic conditions extreme. Thus, to ensure they obtain sufficient energy to fuel daily energetic budgets, birds may need to adjust their diets and become less selective (generalist) as conditions become harsher. To test this hypothesis, we used DNA metabarcoding to characterize both the prey availability (from pitfall traps) and the dietary content (from fecal samples) of several conspecific populations of a semi‐ and arid‐endemic insectivorous bird, the Karoo scrub‐robin ( Cercotrichas coryphaeus ) across a climatic gradient. Our results showed that Coleoptera, Hymenoptera, Orthoptera, and Lepidoptera were the main prey. When accounting for their presence as available prey, Coleoptera and Hymenoptera were preferred in all regions, whereas robins avoided Orthoptera and Lepidoptera in all but the most arid region. Although the different populations live in regions that vary with regards to productivity and thermoregulatory demands, we found that the dietary niche breadth (Bs) of the three populations was intermediate to low, and did not differ significantly. As a whole, our findings show that regardless of environmental harshness these insectivores have similar dietary niches, suggesting that large dietary plasticity is fundamental for their survival in energy‐depauperated ecosystems. Abstract : Our results revealed the spectrum of type IV collagen genes contributing to enrich database resources and had important implications in the diagnosis, prognosis, and guiding treatment of AS.